Optimizing wrist-worn wearable compliance with insights from two Parkinson’s disease cohort studies - Marjan J. Meinders; Laura Heathers; King Chung Ho; Laura Russell; Chris Li; Bastiaan R. Bloem; William J. Marks Jr; Ritu Kapur (npj Parkinson's Disease)
Abstract Wearable technologies enable real-time, continuous, noninvasive data collection, where long-term compliance is essential. The Personalized Parkinson Project (PPP) and the Parkinson’s Progression Markers Initiative (PPMI) utilized the Verily Study Watch. Participants, including people diagnosed with Parkinson’s disease (PD), prodromal PD, and healthy controls, were instructed to wear the watch for up to 23 h daily without data displaying or reporting data back to the participant. Compliance measures and user experiences were evaluated. A centralized support model identified barriers to data collection and enabled proactive outreach. Median daily wear time was 21.9 h for PPP and 21.1–22.2 h per day for PPMI over 2 years. Participants were highly motivated contributing to PD research. These results highlight strategies for achieving strong engagement without providing individual data. This approach offers valuable insights for study designs where returning data to participants could introduce bias or affect the data integrity.